The effect of Polymorphism of the MDR1 (ABCB1) Gene on the Risk of Hepatotoxic Reactions in Patients with Pulmonary Tuberculosis - М. А. Alymenko; R. Sh. Valiev; N. R. Valiev; I. N. Tragira; А. V. Polonikov; N. Р. Balobanova; A. V. Batishchev; V. М. Kolomiets; G. S. Mal; S. N. Volkova; V. V. Kozlov; E. I. Suslikova; et al. (Антибиотики и Химиотерапия)
Currently, a decrease is seen in the effectiveness of treatment in patients with tuberculosis due to the appearance of adverse reactions to anti-tuberculosis drugs. Hepatotoxic reactions play an especially important role in anti-tuberculosis therapy, and phthisiologists often have to deal with the cancellation of a number of anti-tuberculosis drugs. The aim of the study was to investigate the relationship of polymorphic gene variants of xenobiotic biotransformation metabolizing enzymes (NAT2 (590G>A (rs1799930), CYP2E1 (9896C>G (rs2070676), ABCB1 (3435T>C (rs1045642), GSTM1 (E/D), GSTT1 (E/D) with the risk of hepatotoxic reactions in patients with pulmonary tuberculosis. Material and methods. The logistic regression analysis method was used to predict the probability of hepatoxic reactions during specific anti-tuberculosis therapy. Results: 1 statistically significant model was obtained, which reflects the association with hepatotoxic reactions to anti-tuberculosis drugs of the TS genotypes or the TS gene (T allele) ABSV1 (rs1045642). Conclusion. Pharmacogenetic testing used in the study allows us to identify risk groups of patients with pulmonary tuberculosis according to the likelihood of hepatotoxic reactions, which may provide an individualized approach to the treatment of these patients in the future.